Drosophila topoisomerase I: isolation, purification and characterization. - Javaherian, K (1982)
We have purified and characterized topoisomerase I from Drosophila melanogaster. The molecular weight of the enzyme is 135,000; 100,000, 90,000, and 65,000 molecular weight products result from degradation of the enzyme. The enzyme relaxes both positive and negative supercoiled DNA. Mg++ is not absolutely required, but stimulates the enzymatic activity considerably.